"It's My Job Now, I Guess": Biographical disruption and communication work in supporters of young adult cancer survivors. Issue 4 (2nd October 2018) - Iannarino, Nicholas T.
ABSTRACT: This study uses narrative interviews to describe how 25 young adult (YA) close supporters (i.e., romantic partners, siblings) experience an often invisible and uniquely burdensome biographical disruption following a young adult cancer survivor's (YACS; i.e., 18–39) diagnosis. YA supporters reported varying levels of biographical interdependence with the YACS and family system uncertainty with other important supporters. These factors led YA romantic partners and siblings to engage in different types of communication work to negotiate and maintain primary and secondary support roles with parents and in-laws, to ensure that the YACS received helpful social support by gatekeeping (i.e., correcting, blocking) others' support attempts, and to accommodate both their own and the YACS's disrupted biographies.